Characterising suicide-related self-disclosure by peer specialists: a qualitative analysis of audio-recorded sessions. (4th May 2022) - Klim, Casimir; Vitous, C. Ann; Keller-Cohen, Deborah; Vega, Eduardo; Forman, Jane; Lapidos, Adrienne; Abraham, Kristen M.; Pfeiffer, Paul N.
ABSTRACT : Objective: : We characterised peer support specialists' self-disclosures related to suicide and recipient responses to inform services for high-risk individuals that may include peer support. Method: : We used an inductive approach and thematic analysis to identify themes from audio recordings of initial sessions between peer support specialists trained in suicide-related self-disclosure and 10 study participants who were admitted to inpatient psychiatry units with suicidal ideation or a suicide attempt. Results: : The first theme, 'I've been suicidal, but those details are not important', reflects that peers mentioned suicide-related aspects of their histories briefly, often as part of introductions, without participants responding specifically to those aspects. The second theme, 'Being suicidal is one of the challenges I've faced', reflects that in more detailed disclosures by peer specialists and in participant responses, suicide is a part of the mental health challenges and life stressors discussed, not the focus. The third theme 'Let's focus on my recovery and what I've learned' reflects that peers steered their self-disclosures away from suicide and towards what was helpful in their recovery. Conclusions: : Suicide-related self-disclosures embedded within peer specialists' introduction or overall recovery narrative convey a shared experience while focusing the conversation on mental health challenges other than suicide.